Prenatal diagnosis and postnatal outcome of massive abdominal aortic aneurysms—a case report. (16th July 2015) - Bills, Victoria L.; Smithson, Sarah F.; Tsai‐Goodman, Beverly; Tometski, Andrew; Overton, Timothy G.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Vascular aneurysm is an extremely rare fetal abnormality and is usually secondary to genetic defects of vascular development such as Marfan, Loeys–Dietz and Ehler's–Danlos Type IV syndromes. What does this study add? This is the first report of massive fetal aortic aneurysms occurring as a sporadic event, documenting the postnatal pathophysiological consequences and the inadequacy of effective postnatal surgical correction. © 2015 John Wiley & Sons, Ltd.